Concurrent Training Increases Serum Brain-Derived Neurotrophic Factor in Older Adults Regardless of the Exercise Frequency - Canton-Martínez, Ermilo; Rentería, Iván; García-Suárez, Patricia C.; Moncada-Jiménez, José; Machado-Parra, Juan Pablo; Lira, Fabio Santos; Johnson, David K.; Jiménez-Maldonado, Alberto (Frontiers in Aging Neuroscience, 2022)
Background Human brain function declines with aging. In this sense, exercise-based interventions has a promising effect on brain plasticity for older adults. Serum brain-derived neurotrophic factor (BDNF) is a positive biomarker for brain neuroplasticity in healthy older adults also modified by exercise training. Selected features of the exercise prescription for improving brain health are missing; therefore, the aim of this study was to determine the effects of concurrent exercise training frequency on serum BDNF levels in healthy older adults. Methods Nineteen volunteers (age: 65 ± 4 year; body mass index: 28.0 ± 4.5 kg/m2) completed either a three times/week (3-t/w) (n = 8) or five times/week (5-t/w) (n = 11) concurrent exercise program. The exercise program lasted 11 weeks and all exercise sessions were performed for 50 min at moderate intensity. Serum BDNF, body composition, cardiovascular, and physical fitness variables were assessed before and after the exercise training program. Results Regardless of the group, the serum BDNF increased following the intervention (p < 0.001), and there were no significant group (p = 0.827) or interaction (p = 0.063) effects. The maximal oxygen consumption (VO2max) increased regardless of the group (p = 0.007), with a non-significant group (p = 0.722) or interaction (p = 0.223) effects. Upper- and lower-body strength increased in both groups (p = 0.003); however, there was no effect of the training frequency (p = 0.53). For the skeletal muscle mass, there was a trend in the interaction effect (p = 0.053). Finally, the body fat percentage was unchanged. Conclusion Eleven weeks of combined exercise training increased serum BDNF levels in healthy older adults, a response independent of the training frequency. The overall fitness level improved similarly in both exercise groups. These data reveal that a minimal dosage of concurrent exercise enhance functional capacity and a brain health biomarker in older adults.